Abuse of Rachel Carson and Misuse of DDT Science in the Service of Environmental Deregulation. Issue 34 (13th June 2017) - Yang, Jingxiang; Ward, Michael D.; Kahr, Bart
Abstract : Fake news?? The contact insecticide DDT has been reappraised as a safe, life‐saving compound by special interest groups committed to repealing environmental regulations. It is shown in this essay how some specific toxicological data has been misused by those aiming to disingenuously influence public policy. Graphic: Pestroy, a DDT‐laced coating marketed in 1946 by Sherwin‐Williams Research Laboratories.